Penetapan Kadar Protein Secara Kjeldahl Beberapa Makanan Olahan Kerang Remis (Corbiculla moltkiana Prime.) dari Danau Singkarak - Henni Rosaini; Roslinda Rasyid; Vinda Hagramida (Jurnal Farmasi Higea, 2015)
A study on protein content of fresh mussel shells, curry soup mussel shells and fried mussel shells by using Kjeldahl method had been researched. The procedur involve destruction, destilation and titration. Each sample were destructed with consentrated sulfuric acid and catalyst mixture of selenium. The solution of sodium hydroxyde was then added to the resulting solution and the amonia liberated was destilled into solution of hydrochloric acid prepared in excess. Its then the hydrochloric solution was titrated with solution of sodium hydroxide 0.1 N using methyl red as and indicator. Protein content can be calculated by multiplying the total nitrogen content of the sample with protein conversion factor (total nitrogen X 6.25). The highest protein content is fried mussel shells 7.1491 % ± 0.0249, than curry soup mussel shells 6.5771 % ± 0.1095 and the last fresh mussel shells 6.3927 % ± 0.0206.